2009
DOI: 10.26719/2009.15.4.1027
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric gastrointestinal endoscopy: experience in a Sudanese university hospital

Abstract: We investigated the indications for and findings of gastrointestinal (GI) endoscopy in all children ≤ 16 years old referred for the procedure to the endoscopy unit at Soba University Hospital, Khartoum from January 2004 to January 2006. Thus 113 children were enrolled; 73% underwent upper GI endoscopy, 27% lower GI endoscopy (15% colonoscopy, 12% flexible sigmoidoscopy). Indications for upper GI endoscopy included haematemesis (24%), portal hypertension (21%), abdominal pain (16%) and vomiting (15%). Diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 3 publications
3
24
0
Order By: Relevance
“…This finding is higher than in some reports from other developing countries where recurrent abdominal pain constitutes 8 -43% of the endoscopic indications. [6,[10][11][12] Okello et al [13] in Uganda observed that 67.4% of the 135 children undergoing the procedure in a tertiary hospital had recurrent abdominal pain. Recurrent abdominal pain is a common presentation in children and is a frequent reason for referral to the paediatric gastroenterologist with a request for upper GI endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is higher than in some reports from other developing countries where recurrent abdominal pain constitutes 8 -43% of the endoscopic indications. [6,[10][11][12] Okello et al [13] in Uganda observed that 67.4% of the 135 children undergoing the procedure in a tertiary hospital had recurrent abdominal pain. Recurrent abdominal pain is a common presentation in children and is a frequent reason for referral to the paediatric gastroenterologist with a request for upper GI endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In Sudan, upper GI bleeding, especially secondary to PHT, is the most common reason for paediatric upper GI endoscopy. [6] This is believed to be related to the endemicity of schistosomiasis in the country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In various reports, this frequency of abdominal pain is reported to be ranging from 8% to 43%. [12][13][14] In our study, the frequency of abdominal pain as an indication of upper GI endoscopy was 12%. So our results are comparable to other reports from developing countries.…”
Section: Resultsmentioning
confidence: 99%